Archaeological Evidence for the Neolithic Revolution in the Near East - al-Tikriti, Abdul Qadir
M.A.; “A study of the Near East during the era of change-over from the hunting and food collecting economy to the early village farming settlements and their subsequent development until the introduction of Halaf ware in Iraq marks the advent of the full metal age”. Einteilung der Arbeit: I. The Upper Palaeolithic: Palestine and Syria; II. Iraq and Iran; III. Jarmo and the Early Neolithic Phase; IV. Hassuna and the Transition to Chalcolithic Cultures – The Samarran Assemblage and its Relationship with the Halafian and Hassuna Sequences.